The Influence of Financial Transparency and Effectiveness of Internal Supervision on Audit Quality - Linda Asriani; Renny Maisyarah (Proceeding of The International Conference on Business and Economics, 2025)
This study aims to explore and analyze the implementation of internal control mechanisms within Ministries/Agencies that received a disclaimer opinion on their audited financial statements. It also examines the form of financial transparency applied by these institutions in the preparation of their financial reports. The research focuses on the role of government internal audits in two institutions: the Ministry of Marine Affairs and Fisheries and the Indonesian Maritime Security Agency (BAKAMLA), utilizing a qualitative literature synthesis approach. The research method employs a descriptive qualitative design. Based on the findings, it is concluded that the lack of supervision by internal auditors and the Supreme Audit Agency (BPK) over these two institutions stems from several factors: limited competence and capacity of internal auditors, weak internal control systems and structures, lack of auditor independence, and inadequate routine monitoring and evaluation. Furthermore, in preparing financial reports, Ministries and Agencies are required to adopt financial transparency practices by preparing financial statements in accordance with Government Accounting Standards (SAP), disclosing complete notes to financial statements, and utilizing transparent and integrated financial applications.